Case report and review of literature: Resection of a huge mediastinal low-grade fibromyxoid sarcoma with neck, axillary, and lung involvement - Khamashta, Natalie; Dalal, Ahmad; Alashwas, Mo’men; Idkedek, Mayar; Abu-Akar, Firas (Frontiers in Surgery, 2022)
Low-grade fibromyxoid sarcoma is an extremely rare malignant neoplasm, with an incidence of 0.18 per million, and comprises 0.6% of all soft tissue sarcomas. It has a high rate of recurrence and late metastatic spread and is chemotherapy and radiotherapy insensitive. This paper reports a case of an unusually large mediastinal low-grade fibromyxoid sarcoma in a 55-year-old patient. The tumor was engulfing the main blood vessels of the mediastinum, involving the lung, and extending beyond the chest cavity to involve the cervical and axillary regions. The patient has a 21-year history of frequent surgical resections for lesions which were repeatedly misdiagnosed as neurofibroma. The tumor was successfully resected by a challenging operation that involved mediastinal mass resection, chest wall mass resection and wedge resection of the left upper lobe of the lung. The deceivingly benign-looking histology of this tumor makes it a commonly misdiagnosed one, requiring careful assessment by pathologists to reach the right diagnosis. Treatment of choice for these lesions remains surgical resection with clear margins. Due to the behavior of this tumor, once detected and managed, extensive long-term follow up is always recommended.